Unveiling The Contingent Role of Hedonic Value in Predicting The Purchase Intention E-commerce Shopping - Ery Octalina, Lydia; Arifin, Zainul; Rahimah, Anni (FIA UB, 2023)
This research was conducted to determine the impact of utilitarian value and effort expectancy towards purchase intention. In addition, our study also examined how hedonic value moderates the correlation between utilitarian value and purchase intention. This research was a quantitative approach using 150 respondents of Shopee's users. For outer and inner models were analyzed by SEM analysis using the application of Smart-PLS 4th version. Our first finding reveals that utilitarian value significantly influences purchase intention. Then, effort expectancy also has a significant direct influence on purchase intention. The hedonic value couldn’t moderate the correlation between utilitarian value and purchase intention. As a novelty, the researcher used hedonic value as an alternative moderating variable different from previous studies. These results also fulfilled the research gap between effort expectancy and purchase intention in Indonesia's marketplace context. From the result, the researcher advised that Shopee Corporation, one of Indonesia's marketplace providers, could improve their application, especially in ease of usage and providing more benefits to all online users. Public trust could be quickly gained if the corporate maximized this variable in terms of the marketplace in the digital era.